Financing under Extreme Risk: Contract Terms and Returns to Private Investments in Public Equity - Chaplinsky, Susan; Haushalter, David (Review of Financial Studies, 2010)
We study financial contracting using transactions from the private investments in public equity market. Our tests show that the use of terms that are contingent on an issuer’s future performance increases with issuer risk. Among issuers with poorer stock performance, higher cash burn rates, and more uncertain investment prospects, purchase discount-only contracts are uncommon and contracts with contingent terms are frequently used. Our evidence also supports arguments that issuer bargaining power with investors erodes as financing alternatives grow more limited. In particular, terms that can transfer control to investors are most commonly used by issuers in the weakest financial condition.